GUGATAN CERAI SEBAGAI STRATEGI PERLAWANAN PEREMPUAN KORBAN KDRT DI MEDAN, BINJAI DAN DELI SERDANG - Kartika, Silvia Dwi; Daulay, Harmona; Manurung, Ria (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2025)
The phenomenon of divorce has become a widely discussed phenomenon in recent years, especially in cases of divorce by lawsuit. Divorce by lawsuit is the main topic in divorce cases, because there is a fairly high inequality between divorce by lawsuit and divorce by talaq in Indonesia. Divorce by lawsuit actually becomes a boomerang for women, namely the many gender injustices they receive in their households and on the one hand they are labeled as women who are unable to maintain their households. The purpose of this study is to find out how many divorce lawsuits are due to domestic violence, and to see how women interpret the meaning of divorce. This study uses a qualitative method with a case study approach. Data collection used is observation, interviews, and documentation. The objects of this study are women who have been officially divorced in a religious court. The informants in this study were women who sued their husbands for divorce which was legally recorded in the religious court in Medan, Binjai and Deli Serdang. The results of the study showed that 11 out of 15 informants experienced violence in their households, either physically or verbally, even women in Medan, Binjai and Deli Serdang Sumatera Utara, interpreted divorce as a form of resistance that they did for all the injustice they felt. The strong patriarchal culture in society makes women experience a lot of pressure from both family and society.